PENGAWASAN PEMERINTAH DAERAH KOTA PEKANBARU TERHADAP PENGELOLAAN LAMPU PENERANGAN JALAN UMUM(LPJU) - Asido Sumando; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Pekanbaru as a growing city make pekanbaru as centers of trade in goods and services, almost 80 percent of the people to be around the urban environment as reflected in the crowded urban areas, unlike in the urban suburbs.Especially at night, people do a lot of activities and of course have to use state facilities such as street lighting lamps. This facility would be one of supporting the needs of society, especially in the evenings, because a lot of people who work late night make this area very crowded at night and it happens nearly every day. Therefore, the role of local government is required to maintain and provide public facilities so that people become more secure.The problem is there are plenty of street lighting lamps were extinguished it causes various problems occur such as a crime, a robbery, a motorcycle gang that makes people afraid to pass through the streets of the province of the lights were extinguished.Keywords: Government Oversigh